Effect of fertigation on growth, yield, fruit quality and fertilizer-use efficiency of Kiwifruit (Actinidia deliciosa) - Chauhan, Neena; Chandel, J S (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2004 and 2005 to study the effect of fertigation on growth, yield, fruit quality and fertilizer-use efficiency of 18-year-old kiwifruit (Actinidia deliciosa Chev.) vine grown under mid-hill condition of Himachal Pradesh. Four fertigation treatments, viz full, 3/4,1/2 and 1/3 of recommended dose of NPK and recommended dose of NPK as soil application were tried. Fertigation treatments significantly increased the vine growth (155.24 and 168.50 cm), yield (88.00 and 69.65 kg/vine) and fruit quality parameters as compared to soil fertilization. The highest shoot growth (155.24 and 168.50 cm) and trunk girth (2.26 and 2.31 cm) was recorded in fertigation with recommended dose of NPK fertilizers. The fruit yield (88.00 and 69.65 kg/vine), size (71.13mm x 46.59m and 66.74mm x 42.30 mm), weight (79.10 and 72.31g) and quality of fruits, and leaf nutrient contents (2.99 and 3.05 % N, 0.28 and 0.3 1% P, 2.25 and 2.37% K and 0.52 and 0.55 % Mg) were significantly higher under fertigation with recommended dose and 3/4 of recommended dose of NPK compared with the soil fertilization with recommended dose of NPEK and lower doses of NPK applied through drip irrigation. Fertigation with 3/4 of recommended dose of NPK significantly increased the vegetative growth (144.40 and 156.90 cm), fruit yield (86.00 and 65.93 kg/vine), proportion of 'A' grade fruits (58.00 and 36.53 kg/vine), size (70.55mm x 45.25mm and 66.88mm x43.31 mm), weight (78.80 and 71.36 g) and quality of fruits as compared to soil fertilization with a 25% saving of fertilizers. Although the fertilizer-use efficiency was found higher under fertigation with 1/3 of recommended dose of NPK fertilizers, yet the fruit size (65.24mm x 39.13mm and 62.02mm x 38.54 mm), yield (70 0 0 and 58.15 kg/vine) and proportion of 'A' grade fruits (18.00 and 15.20 kg/vine) and net returns (Rs 5 91 408 and Rs 4 86 835 /ha) were significantly reduced compared with the fertigation with full and 314 of recommended dose of NPK fertilizers. Fertigation with 3/4 of recommended dose of NPK fertilizers had higher fertilizer-use efficiency than the recommended dose of NPK applied both through drip and soil application, that gave higher net returns (Rs 10 00 524 and Rs 6 87 747/ha) without affecting the size, yield and quality of fruits.